Accuracy of methods for diagnosing atrial fibrillation using 12-lead ECG: a systematic review and meta-analysis - Taggar, Jaspal S.; Coleman, Tim; Lewis, Sarah; Heneghan, Carl; Jones, Matthew (Elsevier, 2015)
Background: Screening for atrial fibrillation (AF) using 12-lead-electrocardiograms (ECGs) has been recommended; however, the best method for interpreting ECGs to diagnose AF is not known. We compared accuracy of methods for diagnosing AF from ECGs.